The Relationship Between Physical Fitness Levels And Physical Education Learning Outcomes Among Students - Natasya Citra Arum; Maftukin Hudah; Setiyawan Setiyawan (DEPARTEMEN KESEHATAN DAN REKREASI FAKULTAS ILMU KEOLAHRAGAAN, 2026)
This study aims to examine the relationship between physical fitness levels and physical education academic performance among 10th-grade students at SMA Negeri 1 Mranggen, in response to the mixed findings of previous studies, as well as to introduce the digital version of the TKSI Stage E/F instrument, which incorporates sensory-motor components such as hand-eye coordination and visual-motor reaction time. The research design used was quantitative, descriptive-correlational, involving 70 students aged 15–16 years who were selected through simple random sampling. Physical fitness was measured using the TKSI Stage E/F test battery, consisting of six items (hand-eye coordination, hand-touch reaction, agility/vertical jump, arm muscle strength, and the Multistage Fitness Test for VO₂ max), while academic achievement was obtained from midterm exam scores through documentary analysis. The data were analyzed descriptively and tested for normality and linearity prior to hypothesis testing, using Spearman's rank correlation because the data were not normally distributed. The results of the study showed that the students’ average physical fitness score was 21.64 (moderate category), while their average Physical Education (PJOK) learning outcomes were 88 (moderate category). The correlation test yielded an r value of 0.196 with p = 0.104 (p > 0.05), indicating a positive but statistically insignificant and very weak relationship between physical fitness and PJOK learning outcomes. These findings suggest that performance on the midterm exam in physical education, which emphasizes cognitive understanding of sports theory, is more influenced by factors such as teaching methods, memory, and psychological readiness than by students’ physical fitness or motor-sensory abilities alone